Comparative Effectiveness of Merah Putih Cooperatives in Rural and Urban Areas of Ponorogo - Chelsea Meilia Azzahra; Lila Levi Mumpuni (Indonesian Journal of Community Empowerment (IJCE), 2026)
Abstract The Merah Putih Village/Subdistrict Cooperative Program is a national strategic policy aimed at strengthening the community economy through cooperative institutions. This program is supported by a strong legal foundation, including Presidential Instruction Number 9 of 2025 and Law Number 25 of 1992 concerning Cooperatives. Ponorogo Regency is one of the regions with a high implementation rate, marked by the establishment of 307 cooperatives covering all villages and subdistricts. This study aims to analyze the effectiveness of Merah Putih Cooperatives in community economic empowerment through a comparative approach between rural and urban areas. The research uses a descriptive qualitative method supported by secondary data analysis and descriptive statistics. The results show that administratively the program has been effective with 100% coverage, but operationally it remains less than optimal due to the low number of active cooperatives. Urban areas demonstrate better organizational performance, while rural areas possess greater economic potential but face institutional and accessibility constraints. Program Koperasi Desa/Kelurahan Merah Putih merupakan kebijakan strategis nasional yang bertujuan memperkuat ekonomi masyarakat berbasis kelembagaan koperasi. Program ini memiliki landasan hukum yang kuat, antara lain Instruksi Presiden Nomor 9 Tahun 2025 dan Undang-Undang Nomor 25 Tahun 1992 tentang Perkoperasian. Kabupaten Ponorogo menjadi salah satu daerah dengan tingkat implementasi tinggi yang ditandai dengan terbentuknya 307 koperasi di seluruh desa dan kelurahan. Penelitian ini bertujuan menganalisis efektivitas Koperasi Merah Putih dalam pemberdayaan ekonomi masyarakat melalui pendekatan komparatif antara wilayah desa dan kota. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan analisis data sekunder dan statistik deskriptif. Hasil penelitian menunjukkan bahwa secara administratif program telah efektif dengan cakupan 100%, namun secara operasional masih belum optimal karena rendahnya jumlah koperasi aktif. Wilayah kota memiliki kinerja organisasi yang lebih baik, sedangkan wilayah desa memiliki potensi ekonomi yang besar tetapi terkendala kapasitas kelembagaan dan aksesibilitas.